Coaching Competency Strategic Management of Chengdu Wushu Sanda Club - Liang, Qingfeng; Samahito , Supitr (Journal of Roi Kaensarn Academi, 2024)
With the continuous improvement of people’s awareness of health and self-protection, Wushu Sanda sports are increasingly popular. As the core force of the club, the competence of Wushu Sanda coaches is directly related to the learning effect of students and the development of the club. Therefore, I am conducting research on this topic. The objective of this research were to: (1) To study the current situation of coaching competency strategic management of Chengdu Wushu Sanda club. (2) To analyze factors effect Chengdu Wushu Sanda club coaching competency strategic management. (3) To Examine and confirm Chengdu Wushu Sanda club coaching competency strategic management. This research employed a mixed research methodology combining a quantitative and qualitative research methods. The research results show that: (1) The current situation of Coaching competency strategic management of Chengdu Wushu Sanda Club reflects the actual situation of the influencing factors of Coaching competency strategic management of Chengdu Wushu Sanda Club. The improvement of the competence of Wushu Sanda coaches promotes the healthy and sustainable development of the Wushu Sanda industry. Through comprehensive analysis of these factors, the level of coaching competency strategic management of Chengdu Wushu Sanda Club can be further improved. (2) There are five factors: Training, Teaching, Management, Innovation, Self-improvement that have a significant positive impact on coaching competency strategic management of Chengdu Wushu Sanda Club. Among then, (3) It can be seen that the study’s analysis of the current situation survey information and research data on coaching competency strategic management of Chengdu Wushu Sanda Club was unanimously approved. And the quantitative research results all have a certain degree of interpretability, and the structural equation model has good credibility and validity, which has a certain value of promotion.